ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL MATEMATIKA SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Natalia Emanuela Lelboy; Selestina Nahak; Justin Eduardo Simarmata (MES: Journal of Mathematics Education and Science, 2021)
This study aims to identify and describe the erros experienced by students in solfing comparison questions and to determine the causal factors in completing the comparison material for studenst of SMA Stella Gratia Atambua. The research method used is descriptive qualitative method. The subjects in this study were students of class X SMA Stella Gratia Atambua for the 2020/2021 school year. The data collection techniques used were tests and interviews. The instruments in this study was a test item in the form of a description with 3 numbers of questions and an interview guide. Based on the results of the study, it was found that the average error made by students in the type of reading error 33,33%, the comprehension error was the average error percentage of the error was 45%, the transformation error was with The average percentage of errors is 69%, the error in processing skills is 78%, and the encoding error in writing answers is the average percentase of errors is 80 %.